2013
DOI: 10.1111/exd.12285
|View full text |Cite
|
Sign up to set email alerts
|

Internalization routes of cell‐penetrating melanoma antigen peptides into human dendritic cells

Abstract: Optimized delivery of antigens combined with sustainable maturation of dendritic cells (DCs) is crucial for generation of effective antitumoral immune responses. Multiple approaches for ex vivo antigen loading and improvement in immunogenicity have been described. We have recently established a single-step protocol consisting of a fusion peptide (a sequence of the melanoma antigen Melan-A and a cationic cellpenetrating HIV TAT domain) bound in complexes with a tolllike receptor agonist. As the exact cellular u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is now becoming apparent that the uptake could also be via endocytosis [12,37]. To ascertain the mechanism of OVA presentation we have used various inhibitors that can prevent uptake and thereby interfering with the processing and presentation of AntpOVA by DC.…”
Section: Mechanism Of Antpova Antigen Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now becoming apparent that the uptake could also be via endocytosis [12,37]. To ascertain the mechanism of OVA presentation we have used various inhibitors that can prevent uptake and thereby interfering with the processing and presentation of AntpOVA by DC.…”
Section: Mechanism Of Antpova Antigen Presentationmentioning
confidence: 99%
“…Membrane translocating peptides such as the peptide derived from the antennapedia homeodomain or HIV TAT protein have been used to shuttle proteins or peptides into the cytoplasm of antigen presenting cells [13,14,16,[18][19][20]23,24,26,28,30,37,65].…”
Section: Efficient Generation Of Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the ability of CPPs to enhance the immunogenicity of peptide vaccines, we selected eight previously reported sequences that ranged in their hydrophobicity, net charge, length, and origin. We included several CPPs that have been previously reported to augment peptide vaccines: penetratin (pAntp) ( 36 , 39 ), HIV transactivator of transcription (Tat) ( 38 , 44 ), Arg 8 ( 45 ), and MPG ( 46 ). Additionally, this series included CPPs that, to our knowledge, have never been tested for vaccine antigen delivery: Bpep ( 29 ), Diatos peptide vector 6 (DPV6) ( 47 ), vascular endothelial cadherin-derived peptide (pVEC) ( 48 ), and Transportan 10 (TP10) ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although immunogenic responses might be of interest for enhancing immune system responses in immunotherapies for cancer or infectious diseases; they are totally undesirable in case of therapies aimed for attenuating inflammatory and autoimmune responses. It has been reported that some peptides with significant aggregation could affect immunogenicity as it is known that larger particles are more efficiently phagocytised and presented at the membrane level 53 . Activated DCs undergo morphological changes by developing extensions that increase cellular surface area to improve interaction with T cells, as well as upregulate major histocompatibility complex and costimulatory molecules such as CD86 54 .…”
Section: Discussionmentioning
confidence: 99%